SERBIAN FOLK COSTUMES IN TEXTBOOKS OF THE FIRST CYCLE OF EDUCATION (Heritage, 2024)
In the conditions of complex geopolitical changes in the world, the issue of national narratives is an indispensable research topic in various scientific fields. Appreciating various systemic, complex, mutually conditioned approaches to development, in addition to the complexity of the concept of national identity, the representation, appearance character and development of the concept of Serbian national costume, which is observed as an indispensable example of the Serbian national habitus, was observed from the aspect of pedagogy.This paper discusses the following issues: the way Serbian national costume is presented in the textbooks of the first cycle of education, and whether it is a formal or essential approach to the construction of the comprehensive idea of national identity. The author's research attention is focused on 24 textbooks of Science and social studies and Music (three publishers) for the first four grades of primary school.The findings have shown that the Serbian national costume is insufficiently, unsystematically, formally, often incorrectly presented in the analyzed textbooks, at the representative level; visual representations dominate over textual description, questions, tasks and requests; the content dimensionality and development of the concept in terms of intensity and extent were not noticed; it has been shown that there is no horizontal and vertical systemic content correlation.
Keywords: national identity, education, intangible cultural heritage, Science and social studies, Music